Kærlighedens kunst. Om Kieslowskis film og lidt om Aleksandra Kollontaj - Svendsen, Erik (Kvinder, Køn & Forskning, 1998)
The article deals with the contruction of the conception of romantic love in the productions of the Polish film director Kieslowski. Erik Svendsen discusses the idea of romantic love as a silent criticism of the authoritarian regimes in Eastern Europe and points out, too, the similarities to the Communist interpretation of love as it was perceived and proclaimed by Alexandra Kollontay. The heritage of Kieslowski is the cultural heritage of both Communism and Catholicism in Poland.